Autologous stem cell transplantation for patients with viral hepatitis-induced liver cirrhosis: a systematic review and meta-analysis. Issue 10 (October 2019) - Chen, Bin; Pang, Long; Cao, Hongxin; Wu, Dongbo; Wang, Yonghong; Tao, Yachao; Wang, Menglan; Chen, Enqiang
Abstract : Background: Recently, stem cells have been used in the treatment of viral hepatitis-induced liver cirrhosis (LC), and stem cell therapy is showing potential therapeutic effects on liver function improvement. The consensus on effects and safety of stem cell therapy has not been reached, thus it is essential for us to conduct a systematic review and meat-analysis to investigate the efficacy and safety of stem cell therapy for viral hepatitis-induced LC. Materials and methods: Medline, Embase, SinoMed and Cochrane Library databases were searched with appropriate keywords through 5 August 2018. We included eight trials involving 467 patients. The pooled weight mean difference (WMD) and 95% confidence interval (CI) were calculated using a fixed or random effects model. Quality assessment and publication bias were also performed. The selected studies were considered for meta-analysis using RevMan V5.3. Results: Compared with traditional therapy group, autologous stem cell transplantation increased the level of albumin (WMD: 2.47, 95% CI: 1.05–3.90, P < 0.001), but decreased the level of total bilirubin (WMD: −2.26, 95% CI: −3.61 to −0.90, P = 0.001), alanine aminotransferase (WMD: −9.16, 95% CI: −16.47 to −1.85, P = 0.01) and prothrombin time (WMD: −3.02, 95% CI: −4.83 to −1.22, P = 0.001). Clinical symptoms such as edema, fatigue, anorexia and abdominal distention were alleviated. Model for End-Stage Liver Disease and Child–Pugh scores were decreased after stem cell therapy. Whereas, there was no statistically significant difference between two groups regarding aspartate aminotransferase, prothrombin time activity, ascites and pleural fluid. No procedure-related complications were found. Conclusion: Autologous stem cell transplantation might have beneficial effects on patients with viral hepatitis-induced LC and is relatively safe for these patients. Further high-quality randomized controlled trials are needed.